Migration Intentions оf Secondary Vocational education students in Stavropol Krai and Dagestan - Ju. F. Zolnikova; I. A. Soloviev; N. A. Shchitova; P. M. Polyan (Наука. Инновации. Технологии, 2024)
The study considers territorial features of migration and migration intentions of student youth of Stavropol Krai and the Republic of Dagestan, the relevance of which is due to the increased migration mobility of young people, which is determined by life plans after graduation. The study is based on the analysis of statistical data of a mass online survey of students of secondary vocational educational institutions. The sample of respondents was more than 2,100 people. To conduct a sociological study, a special questionnaire was developed with “open” and “closed” types of questions. The study included consideration of push and pull factors of migration, as well as the qualitative composition of respondents. The study showed similar features of migration and migration intentions of student youth of Stavropol Krai and the Republic of Dagestan, which, first of all, depend on the “center-periphery” positioning of territories. Within Russia, the greatest attractiveness for potential migrants pose Moscow, St. Petersburg, Rostov- on-Don and Krasnodar Krai. Within the regions under study, the maximum direction of migration intentions is associated with the administrative centers - Stavropol and Makhachkala. An important difference of Stavropol Krai is its greater attractiveness for educational migrants from outside the region, which is associated with the peculiarities of its geographical location, ethnic and ethnodemographic processes and the level of socio-economic development. In turn, a specific feature of the migration intentions of student youth in the Republic of Dagestan is the higher attractiveness of the respondents' small homeland, which is associated, in our opinion, with the traditional foundations of society in the region. To curb the outflow of youth from the regions under study, first of all, comprehensive socioeconomic development of the territories is necessary.